Monopoly In Islamic Perspective And Its Application In Life - Sahmiar Pulungan (Proceeding International Seminar of Islamic Studies, 2019)
Monopoly in muamalat means al-Ihtikar, in etymology is the act of hoarding, collecting (goods) or a place to hoard. Ulama has different perspective of hoarding objects. Shafi'i and al-Gazali mahzab argued that hoarding was only found in the primary material according to the Hanafi Mahzab found by and other opinions ihtikar is generally applicable, namely hoarding all goods human needs, both primary and secondary, which become 'illat for this school are the affluence that afflicts many people, encompassing all the products that people need as a whole. In the principles of Islamic law, whatever is permissible by Allah to have it, then halal is used as an object of trade. Likewise all forms which are forbidden to have it are forbidden to be traded. But in Islam in principle the item is lawful, but because the attitudes and actions of the perpetrators are contrary to the shari'ah, the goods from the critical side turn into haram. In this paper, a qualitative method is used. To avoid monopoly in the society, it is needed the role of government to avoid monopoly practices.